Association of Gender to Mandibular Second Molars with Single Fused Canal: A Retrospective study - GULZAR, RUKHSAAR; RANJAN, MANISH; MAHALAKSHMI, J (The journal of contemporary issues in business and government, 2021)
The occurrence of aberrant anatomy is one of the causes of endodontic failures when they are not detected accurately. Hence understanding these anomalies is highly important for a dental practitioner. The present retrospective study was conducted to analyse the incidence of a single fused canal in mandibular second molars and its association with gender . Data was obtained from the database of the institute and the preoperative and obturation radiographs were evaluated. The details were entered in an excel sheet and a descriptive statistical analysis and a chi square test by SPSS. The results of the present study showed a 1.6% chance of occurance of a single fused root with a single canal in a mandibular second molar with a higher predilection for females. These results are statistically significant with a p value of 0.012. From a clinical point of application, a complete examination from multiple angled radiographs and three dimensional assessment must be conducted when an unusual anatomic form is encountered. This will reveal accurate details and will help in preventing iatrogenic errors which often lead to the failure of endodontic treatment.